A Latent Class Analysis of Manic and Psychotic Symptoms. Issue 9 (September 2020) - Pignon, Baptiste; Peyre, Hugo; Noblins, Emmanuel; Rolland, Benjamin; Thomas, Pierre; Vaiva, Guillaume; Roelandt, Jean-Luc; Benradia, Imane; Amad, Ali; Geoffroy, Pierre A.
Abstract : Abstract: Bipolar spectrum disorders encompass heterogeneous clinical manifestations and comorbidities. A latent class analysis (LCA) was performed in 1846 subjects who experienced an episode of abnormally elevated or irritable mood to identify homogeneous groups of subjects, based on the distribution of 11 manic and 7 psychotic symptoms. LCA identified five classes: 1) two classes with irritability and with low and high level of psychosis (respectively "irritable, " 29.1% of the sample, and "irritable-psychotic, " 16.2%); 2) a class with expansive mood and hyperactivity ("expansive-hyperactive, " 12.7%); and 3) two classes with manic symptoms and high and low level of psychosis ("manic-psychotic, " 15.0%, and "manic, " 27.2%). "Irritable" displayed lower rates of depressive episode, panic, and substance use disorders. Manic-psychotic displayed higher rates of depressive episode, panic, generalized anxiety, and substance use disorders. Use of mental health treatment more frequent in manic-psychotic and manic classes. Five classes of bipolar spectrum disorders were characterized by different sociodemographic and clinical patterns. Abstract : Supplemental digital content is available in the text.